Atmospheric oxidation of Folpet initiated by OH radicals, NO3 radicals, and O3. Issue 4 (11th January 2021) - Zhang, Chenxi; Sun, Xiaomin; Tan, Wei; Peng, Hengjun
Abstract : The fate of Folpet is dictated by oxidation initiated by atmospheric oxidants such as O3, OH, and NO3 radicals. Considering the oxidant concentration in the atmosphere, Folpet seems to be mainly scavenged by NO3 radicals, especially at night. Abstract : Folpet, a nonspecific sulfenimide fungicide, is widely used to protect crops against mildew. It can be dispersed and transported over long distances. The residence time of Folpet in the atmosphere depends on the oxidation processes initiated by atmospheric oxidants such as O3, OH and NO3 radicals. In this study, the reactions of Folpet with gas-phase O3, OH and NO3 radicals were investigated via quantum chemical calculation methods, which can effectively provide information about the reaction intermediates and pathways. The obtained results show that the room-temperature rate constants of the reactions between Folpet and OH radicals, NO3 radicals and O3 are about 3.69 × 10 −14, 5.40 × 10 −15, and 1.73 × 10 −22 cm 3 per molecule per s at 298 K, respectively. Considering the oxidant concentration in the atmosphere, Folpet seems to be mainly scavenged by NO3 radicals, especially at night. This study can contribute to a better understanding of the atmospheric fate of Folpet, elucidating a significant impact of NO3 radicals on its degradation process in comparison with other oxidants such as O3 and OH radicals.